Nanoconfined Gas Flow Behavior in Organic Shale: Wettability Effect - Shan Wu; Xiaorui Wang; Ying Yu; Yao Yu; Liang Zhang; Ran Mao (Geofluids)
A clear understanding of nanoconfined gas flow behavior in shale gas reservoirs is beneficial for its efficient development. Nanopores in the shale gas reservoirs are characterized by complex surface chemistry and composition, as well as affinity, while their impact on methane flow has not been investigated comprehensively before. In light of current research status, this article proposes a simple yet robust theoretical model, incorporating bulk-gas flow flux and surface diffusion of adsorption gas. In particular, wettability effect, indicating the influences of the shifted critical properties and adsorption thickness, is captured as well. In this article, gas physical attributes, such as gas compressibility factor and gas viscosity, are modified under the nanoconfinement effect and wettability effect, and also the variation of effective pore size, induced by surface wettability, is considered. Notably, wettability effect in this article is described by using a macroscopic form, surface contact angle, facilitating the model applicability. In addition, both the bulk-gas flow model and surface-diffusion model, developed in this research, are able to achieve excellent agreements compared with the existed documents, clarifying the reliability of the proposed model. Meanwhile, key role of wettability effect on nanoconfined gas flow behavior, especially for surface diffusion of adsorption gas, is demonstrated. Results show that (a) the gas flux in small nanopores may exceed that in large nanopores, due to the predominant role of surface diffusion, while pore size is less than 10 nm; (b) the absence of real gas effect will lead to inaccurate characterization of nanoconfined gas flow capacity, and the magnitude can reach 7% for pore size of 5 nm and will enlarge with further pore size shrinkage; (c) wettability effect governs the total gas flux when pore size is less than 10 nm, while its impact will be greatly mitigated when pore size is greater than 50 nm. This article provides a comprehensive investigation to shed light on surface wettability on gas flow behavior through nanopores.